Sociokulturni pristop pri spremljanju otrokovega razvoja in učenja v vrtcu - Rutar, Sonja (Revija za elementarno izobraževanje, 2013)
Sociocultural Approach to Assessment of Child Development and Learning in Preschool Education. Assessment is integral to preschool curriculum. Within contemporary preschool pedagogy, the assessment of child development and learning, which represents a basis for curriculum planning, is considered one of preschool standards of quality. In this paper, we present the difference between scientific observation which is based on developmental psychology, and the pedagogical assessment of child development and learning. We outline the purpose of assessing child development and learning in early childhood and introduce two different approaches to assessment, namely, the decontextualised approach which focuses on monitoring a child out of the context and the sociocultural approach which aims to identify and understand a child and his or her learning in the physical and the social context.